H3K4me3 Histone ChIP-Seq Analysis Reveals Molecular Mechanisms Responsible for Neutrophil Dysfunction in HIV-Infected Individuals - Piatek, Paweł; Tarkowski, Maciej; Namiecinska, Magdalena; Riva, Agostino; Wieczorek, Marek; Michlewska, Sylwia; Dulska, Justyna; Domowicz, Małgorzata; Kulińska-Michalska, Małgorzata; Lewkowicz, Natalia; Lewkowicz, Przemysław (Frontiers in Immunology, 2021)
Peripheral neutrophils in HIV-infected individuals are characterized by impairment of chemotaxis, phagocytosis, bactericidal activity, and oxidative burst ability regardless of whether patients are receiving antiretroviral therapy or not. Neutrophil dysfunction leads not only to increased susceptibility to opportunistic infections but also to tissue damage through the release of reactive oxygen species (ROS), proteases and other potentially harmful effector molecules contributing to the AIDS progression. In this study, we demonstrated high expression of histone H3 lysine K4 trimethylated (H3K4me3) and dysregulation of DNA transcription in H3K4me3 histone in circulating neutrophils of the patients infected with HIV. This dysregulation was accompanied by deficient response of neutrophils to LPS, impaired cytokine/chemokine/growth factor synthesis as well as increased apoptosis. Chromatin immunoprecipitation sequencing (ChIPseq) H3K4me3 histone analysis revealed that the most spectacular abnormalities were observed in the exons, introns and promoter-TSS regions. Bioinformatic analysis of Gene Ontology, including biological processes, molecular function and cellular components, demonstrated that the main changes were related to the genes responsible for cell activation, cytokine production, adhesive molecule expression, histone remodeling via upregulation of methyltransferase process and downregulation of NF-kB transcription factor in canonical pathways. Abnormalities within H3K4me3 implicated LPS-mediated NF-kB canonical activation pathway that was a result of low amounts of kB DNA sites within histone H3K4me3, low NF-kB (p65 RelA) and TLR4 mRNA expression as well as reduced free NF-kB (p65 RelA) accumulation in the nucleus. ‘Panoramic view of the landscape gene’ within histone H3K4me3 led us postulate that impairment within the canonical NF-kB cell activation pathway may be the primary phenomenon responsible for neutrophil dysfunction observed in HIV-infected individuals.